ANALISIS EFEKTIVITAS REALISASI RETRIBUSI DAERAH SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BULELENG - Wibawa, I Kadek Surya Wibawa; Werastuti, Desak Nyoman Sri (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
The purpose of the study conducted was to measure the effectiveness of the realization of the levy and the contribution to PAD and find out the factors that resulted in the non-achievement of the regional levy target and how to overcome obstacles that resulted in the non-achievement of the regional levy target. The research method used is qualitative descriptive analysis. The analysis carried out shows that the effectiveness of the Regional Levy of Buleleng Regency in 2017 - 2021 has not been maximized because its effectiveness is still below 100%. In addition, his contribution to PAD is sorely lacking. The factors that result in the non-achievement of the regional levy target are inadequate facilities, lack of inadequate human resources services, and lack of socialization, economic factors and low public awareness. Ways to overcome these obstacles are to budget funds to improve or improve facilities, improve services, provide training, and maximize socialization and increase awareness of the importance of regional levies.